Pemanfaatan Kecerdasan Buatan untuk Inovasi Pemasaran dan Keberlanjutan Bisnis Oleh Oleh Smakelijk - Ronald Farrell Wardhana; Iva Nurdiana Nurfarida; Yoan Santosa Putra (Journal of Economics and Management Scienties, 2026)
The culinary souvenir industry in Surabaya faces competitive challenges that demand digital transformation in the era of Society 5.0. This research aims to formulate AI-based marketing innovation strategies to support the business sustainability of "Oleh Oleh Smakelijk." Using a mixed methods approach with an explanatory sequential design, this study integrates data from a Systematic Literature Review (SLR) of 25 reputable articles and qualitative case studies through interviews and field observations. The results of the problem identification indicate that dependency on manual processes leads to slow service responses and stock fluctuations resulting in product waste, a condition that does not align with the preferences of Generation Z consumers. The research recommends the implementation of three AI components: Generative AI for content personalization, Chatbots for customer service automation, and Predictive Analytics for inventory management. The application of these strategies is projected to reduce product waste by 15% and improve operational efficiency. The main conclusion of this study is that adopting a "Hybrid Intelligence" model, which combines human touch in products with machine intelligence in marketing, is essential for SMEs to enhance profitability and achieve economic and environmental sustainability goals.